Triple-based teaching approach: ‘student as manager’ model in business studies (evaluation and result) - Nallaluthan, Kesavan; Suhaimi, Suhazlan; Gopal, Revathi; Zainal, Mazlan (Ifma Publishing, 2022)
The triple-based teaching approach is a student-center learning process that is implemented for undergraduate business studies. It is mixed with the game, problem, and challenge-based learning strategy that aims to prepare business students to manage unexpected and complex global or industrial issues in the 21st century. It encourages an active and reliable learning environment that requires students' creative input, collaboration, and industrial involvement. The action research method applied for this Triple-based teaching approach which implements the ‘Student as Manager’ model with a relevant task for undergraduate business students at Universiti Pendidikan Sultan Idris (UPSI). Therefore, for the pilot test the Strategic Management subject (PPB3073) A191 semester selected to implement this teaching approach. Overall result Course Learning Outcome (CLO) shows that 75.1 percent and this subject overall performance was 95.46 percent. This teaching approach beneficial for undergraduate students to getting know about industrial phenomena with 21st learning skills (collaborative, creative, critical thinking, and communication).